Pengaruh pre-strain dan tegangan listrik terhadap sifat fisik mekanik dan korosi sambungan las titik (RSW) logam beda jenis antara AISI 430 dan JSL AUS (J1) - Arief Ari Kuntoro; Triyono .; Heru Sukanto (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
Distortion often occurs in thin plate welding process. Pre-strain is ussualy choosen for repairing those failure. Pre-strain is the method which stretchs and holds the material before welding process. The main objective of this research is to investigate the effect of pre-strain and voltage on corrosion, physic and mechanics properties of dissimilar metals spot welded between AISI 430 and J1. Variation of pre-strain treatment is (0%; 0.2%; 0.5%; 1%) and voltage is (1.60V; 1.79V; 2.02V; 2.30V). Electrode pressure force is 500N. NaCl 3.5% solution is used for potentiodynamic polarization corrosion test. As a result of the experiment showed that nugget size enlarge with increasing voltage which cause pullout failure mode. Nugget size decrease after pre-strain was applied to the specimen and makes interfacial failure mode. Variation of pre-strain at 1% and voltage at 2.30V had the highest corrosion rate of 0.0497 mm/y. Pitting corrosion is the corrosion which occurs in the specimen. Pitting corrosion occurs due to overheating when welding with pre-strain treatment cause the protective oxide passive film layer from AISI 430 was damaged.